Optimization time and energy efficiency of maritime cyclic vacuum wood drying through A theoretical model of heat and moisture transfer - Yuqing Ding; Hua Qian (Energy Conversion and Management: X)
Utilizing ship engine waste heat for convective cyclic vacuum drying of wood during maritime transport offers an efficient, eco-friendly alternative to conventional drying, addressing challenges like space, energy, time, and environmental impact. However, limitations include transportation time, waste heat availability, and reliance on manual control, which may cause drying defects. This study develops a one-dimensional model based on the boiling front concept, simplified using the diffusion equation, to describe heat and moisture transfer. Solved via the finite volume method in MATLAB, the model predicts drying dynamics for 42.12 m3 of Larix gmelinii, reducing moisture content from 40 % to 23 % with 9.022 × 107 kJ over two cycles: 70 min heating/560 min vacuum, then 66 min heating/11 days vacuum. Findings enable rapid prediction of drying time and energy for various species and conditions, supporting automated control and adapting to shipping route changes, advancing the timber drying industry.